SECURING THE DIGITAL FRONTIER: BEST PRACTICES FOR RESTFUL API PROTECTION IN MODERN WEB APPLICATIONS - Prakash Raj Ojha (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This article presents a comprehensive analysis of security best practices for RESTful APIs in modern web applications, with a particular focus on microservices architectures. As web applications become increasingly distributed and API-driven, the need for robust security measures has never been more critical. We examine the implementation of contemporary authentication and authorization frameworks, including OAuth2 and OpenID Connect, and their role in securing API endpoints. The article delves into strategies for protecting data through encryption, both at rest and in transit, and explores the importance of secure communication protocols. We also investigate the implementation of rate limiting and throttling mechanisms to prevent API abuse and ensure system stability. Furthermore, the article highlights the significance of continuous monitoring, logging, and auditing in maintaining API security. By synthesizing current research and industry standards, we provide a holistic framework for securing RESTful APIs that balances the need for accessibility with stringent protection measures. This article contributes to the ongoing discourse on web application security and offers practical insights for developers and architects working with API-centric systems in an era of increasing cyber threats.